Proteolipid protein modulates preservation of peripheral axons and premature death when myelin protein zero is lacking. Issue 1 (22nd September 2015) - Patzig, Julia; Kusch, Kathrin; Fledrich, Robert; Eichel, Maria A.; Lüders, Katja A.; Möbius, Wiebke; Sereda, Michael W.; Nave, Klaus‐Armin; Martini, Rudolf; Werner, Hauke B.
Abstract : Protein zero (P0) is the major structural component of peripheral myelin. Lack of this adhesion protein from Schwann cells causes a severe dysmyelinating neuropathy with secondary axonal degeneration in humans with the neuropathy Dejerine‐Sottas syndrome (DSS) and in the corresponding mouse model ( P0 null ‐mice). In the mammalian CNS, the tetraspan‐membrane protein PLP is the major structural myelin constituent and required for the long‐term preservation of myelinated axons, which fails in hereditary spastic paraplegia (SPG type‐2) and the relevant mouse model ( Plp null ‐mice). The Plp ‐gene is also expressed in Schwann cells but PLP is of very low abundance in normal peripheral myelin; its function has thus remained enigmatic. Here we show that the abundance of PLP but not of other tetraspan myelin proteins is strongly increased in compact peripheral myelin of P0 null ‐mice. To determine the functional relevance of PLP expression in the absence of P0, we generated P0 null * Plp null ‐double‐mutant mice. Compared with either single‐mutant, P0 null * Plp null ‐mice display impaired nerve conduction, reduced motor functions, and premature death. At the morphological level, axonal segments were frequently non‐myelinated but in a one‐to‐one relationship with a hypertrophic Schwann cell. Importantly, axonal numbers were reduced in the vital phrenic nerve of P0 null * Plp null ‐mice. In the absence of P0, thus, PLP also contributes to myelination by Schwann cells and to the preservation of peripheral axons. These data provide a link between the Schwann cell‐dependent support of peripheral axons and the oligodendrocyte‐dependent support of central axons. GLIA 2016;64:155–174 Main Points: PLP is strongly enriched in compact PNS myelin of P0 null ‐mice. Compared to either single‐mutant, P0 null *Plp null ‐mice show impaired myelination, axon numbers, nerve conduction, and early death. PLP mitigates against the consequences of P0 deficiency.